A Lagrangian cell‐centred finite volume method for metal forming simulation. (7th September 2016) - Cardiff, P.; Tuković, Ž.; Jaeger, P. De; Clancy, M.; Ivanković, A.
Summary: The current article presents a Lagrangian cell‐centred finite volume solution methodology for simulation of metal forming processes. Details are given of the mathematical model in updated Lagrangian form, where a hyperelastoplastic J 2 constitutive relation has been employed. The cell‐centred finite volume discretisation is described, where a modified discretised is proposed to alleviate erroneous hydrostatic pressure oscillations; an outline of the memory efficient segregated solution procedure is given. The accuracy and order of accuracy of the method are examined on a number of 2‐D and 3‐D elastoplastic benchmark test cases, where good agreement with available analytical and finite element solutions is achieved. Copyright © 2016 John Wiley & Sons, Ltd.